2003
DOI: 10.1590/s0103-97332003000400017
|View full text |Cite
|
Sign up to set email alerts
|

The unusual morphology, structure, and magnetic property evolution of glassy carbon upon high pressure treatment

Abstract: Glassy carbon (GC) has been high-pressure high-temperature treated. An interesting morphology evolution from the pristine sample to the high pressure products was observed. It is found that GC can be graphitized under pressure at a temperature much lower than that at ambient condition. Furthermore the in − situ structure and electrical measurements of GC and graphitized glassy carbon (GGC) under high temperature and high pressure have been investigated up to 30 GPa. We particularly emphasize the unusual magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Therefore, we conclude that graphene layers grown at low temperatures (720-744 C) form a disordered stack similar to a turbostratic structure because it needs high-temperature ($2700 C) or low-temperature ($1400 C) annealing under high pressure condition ($5 GPa) for the crystallization of graphite having a turbostratic structure 25,26) and glassy carbon. 28) We also observed that the D-band intensity increases with growth. 21) The grain size evaluated from the G/D ratio is about 50 nm.…”
Section: Resultssupporting
confidence: 56%
“…Therefore, we conclude that graphene layers grown at low temperatures (720-744 C) form a disordered stack similar to a turbostratic structure because it needs high-temperature ($2700 C) or low-temperature ($1400 C) annealing under high pressure condition ($5 GPa) for the crystallization of graphite having a turbostratic structure 25,26) and glassy carbon. 28) We also observed that the D-band intensity increases with growth. 21) The grain size evaluated from the G/D ratio is about 50 nm.…”
Section: Resultssupporting
confidence: 56%
“…The background is skew, the peaks are broad and asymmetric, and there are no peaks that characterize the threedimensional periodicity of a perfect graphite-like structure. These features were also found in the diffraction patterns of the onion-like carbons [24][25] and glassy carbon [26]. The dilation of the layered structure along the c-axis can explain the broadening and the shift of the first peak Though the XRD patterns of the bulk and HIP-produced samples look similar, there is a difference.…”
Section: Resultsmentioning
confidence: 70%
“…100 nm, while its developed structure resembles that obtained for BCNW grown on flat surfaces [ 41 ]. The XRD pattern reveals GC-originating peaks (2q~26°), broad due to the disordered character of the graphite layers [ 62 ]. The above peaks are overlapped by BCNW-originating (100) graphene facets, with (110) facets also present at approx.…”
Section: Resultsmentioning
confidence: 99%